Usmeritve za obvladovanje smrekovih lubadarjev - Jakša, Jošt (Gozdarski vestnik, 2008)
This article describes actions, methods and techniques for the bark beetle control. We divide the activities into the preventive and suppressive ones. Weuse technical, biotechnical and chemical methods or their combination. Thorough knowledge of stand condition, bark beetle biology and bark beetle control methods represent a condition for the work success and reduction of damage caused in forests by bark beetles. The topic of this article is limitedto the eight-toothed spruce bark beetle (Ips typographus L.) and six-toothed spruce bark beetle (Pityogenes chalcographus L.) control.
Keywords: podlubniki; smrekov lubadar; zatiranje